(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2019)
Studies on trophic ecology allow to understand the role that each species fulfill and the impact that their disappearance or population decrease could have on the ecosystem one hundred fiftyfive stomachs of Ariopsis guatemalensis obtained from the Salado Estuary of Guayaquil were analyzed, to determine the Fullness Index, Index of Relative Importance of prey (%IRI), feeding strategy (Levins Index and Graphical Amundsen et al Method) and trophic levels (TROPH) for both sexes. Females were classified in four size intervals to determine the difference in diet. Females presented 83% of full stomachs, while 73% males were empty due to gonadal maturation and oral incubation events. In total, 18 prey items were identified, Penaeus vannamei (35.3%) and Goniopsis sp. (32%) being the most important prey. For females, P.vannamei and Goniopsis sp. were the most important prey and in males, were Goniopsis sp. and decapod eggs. Different female sizes showed similarity (r ≥ 0.58) in diet, with P. vannamei, Goniopsis sp. and Ocypodidae sp. being the most important in all sizes; while other preys are proportionately consumed, without intraspecific competition. The TROPH method determined that A. guatemalensis is a carnivorous species of second and third trophic level, with mixed feeding strategy for both sexes, being females specialized in P. vannamei and Gonipsis sp; and males Goniopsis sp. and decapod eggs (Ba <0.6).